FORMATION PROCESSES OF FRAMBOIDAL PYRITE - Wilkin R.T.; Barnes H.L. (My University, 1997)
Pyrite framboid formation may be the result of four consecutive processes: (1) nucleation and growth of initial iron monosulfide microcrystals; (2) reaction of the microcrystals to greigite (Fe3S4; (3) aggregation of uniformly sized greigite microcrystals, i.e., framboid growth; and (4) replacement of greigite framboids by pyrite. The uniform morphology, uniform size range, and ordering of the microcrystals in individual framboids, as well as the range of observed framboid structures from irregular aggregates to densely packed spherical aggregates and polyframboids, are consequences of these processes. Using DLVO theory (Derjaguin, Landau, Verwey, and Overbeek), we have evaluated the stability of colloidal, iron monosulfide suspensions with ionic strengths typical of marine and lacustrine waters. In addition to van der Waals attractive and double-layer repulsive forces, a term is included to account for the ferrimagnetic properties of greigite. Numerical models predict that magnetically saturated greigite particles >0.1 μm in diameter will rapidly aggregate in either marine or fresh water. The aggregation model is in agreement with the sequence of greigite formation followed by pyrite framboid formation established in a previous experimental study (Sweeney and Kaplan, 1973) and is consistent with the occurrence of framboids composed of other magnetic minerals, e.g., greigite, magnetite, and magnesioferrite. Based on the temperature-dependent magnetic properties of greigite and aging experiments in hydrothermal solutions, this mechanism for framboid formation via precursor greigite could operate to temperatures of ~200°C, consistent with the occasional occurrence of pyrite framboids in the paragenesis of metalliferous ore deposits.